Involvement of transforming growth factor alpha in the release of luteinizing hormone-releasing hormone from the developing female hypothalamus. - Ojeda, S R (1990)
Little is known about the presence of trophic factors in the hypothalamus and the role they may play in regulating the functional development of hypothalamic neurons. We have investigated the ability of epidermal growth factor (EGF) and transforming growth factor alpha (TGF-alpha) to affect the release of luteinizing hormone-releasing hormone (LHRH), the neuropeptide that controls reproductive development. We have also determined whether the genes encoding EGF and TGF-alpha are expressed in the prepubertal female hypothalamus. Northern blot analysis of poly(A)+ RNA utilizing a single-stranded EGF cDNA probe failed to reveal the presence of EGF mRNA in either the hypothalamus or the cerebral cortex at any age studied (fetal day 18 to postnatal day 36). In contrast, both a complementary RNA probe and a double-stranded TGF-alpha cDNA recognized in these regions a 4.5-kilobase (kb) mRNA species identical to TGF-alpha mRNA. The abundance of TGF-alpha mRNA was 3-4 times greater in the hypothalamus than in the cerebral cortex. Both EGF and TGF-alpha (2-100 ng/ml) elicited a dose-related increase in LHRH release from the median eminence of juvenile rats in vitro. They also enhanced prostaglandin E2 (PGE2) release. The transforming growth factors TGF-beta 1 and -beta 2 were ineffective. Only a high dose of basic fibroblast growth factor was able to increase LHRH and PGE2 release. Blockade of the EGF receptor transduction mechanism with RG 50864, a selective inhibitor of EGF receptor tyrosine kinase activity, prevented the effect of both EGF and TGF-alpha on LHRH and PGE2 release but failed to inhibit the stimulatory effect of PGE2 on LHRH release. Inhibition of prostaglandin synthesis abolished the effect of TGF-alpha on LHRH, indicating that PGE2 mediates TGF-alpha-induced LHRH release. The results indicate that the effect of EGF and TGF-alpha on LHRH release is mediated by the EGF/TGF-alpha receptor and suggest that TGF-alpha rather than EGF may be the physiological ligand for this interaction. Since in the central nervous system most EGF/TGF-alpha receptors are located on glial cells, the results also raise the possibility that--at the median eminence--TGF-alpha action may involve a glial-neuronal interaction, a mechanism by which the trophic factor first stimulates PGE2 release from glial cells, and then PGE2 elicits LHRH from the neuronal terminals.